Using Schottky Arc-plasma for Modelling the Cathode Temperatures of Various Materials at High Pressure - Mohamed, Zainab Majeed; Ali, Rafid Abbas (Iraqi Journal of Science, 2024)
Theoretical investigation for cathodes of different metals, including hafnium (Hf), niobium (Nb), tungsten (W), and molybdenum (Mo) were used. It was noticed that the plasma energy at the cathode (Hf) has a higher value than that at the cathode metal because the energy losses of electrons for (Hf) are less due to inelastic collisions. As for the energy of electrons, their value for the metal (Hf) is also higher than of the other metals, and the reason is that the energy is proportional to the temperature according to the equation: (E = 3/2 KT). It was also noted that the energy of ions for all metals is almost equal at temperature (Tw≅4000K) due to energy losses due to elastic and inelastic collisions, this leads to a state of saturation. There is a large decrease in the voltage barrier accompanied by an increase in the current density, differences occur in the values of the voltage barrier due to the difference in the work function which varies according to the metal.